HUBUNGAN CITRA MEREK (BRAND IMAGE) DENGAN KEPUTUSAN PEMBELIAN SEPATU WANITA MEREK ROHDE PADA PT. MAHKOTA JAYA SENTOSA CABANG MATAHARI MALL SKA - Kurniawan, Teuku Reza (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This study aims to determine the effect of brand image on purchasing decisions for women's shoes with the Rohde brand at PT. Mahkota Jaya Sentosa Matahari Mall SKA Branch. By using a sample of 98 people. In this research, the writer uses incidental sampling research method using the SPSS method.  From  the  results  obtained,  the  variable tcount  of  brand  image is 5.484 and the value of ttable is 1.66088. so that tcount>ttable (5.484 > 1.66088) and a significant value of 0.000 <0.05, so it can be said that the brand image variable has a positive and significant effect on purchasing decisions. In testing the coefficient of determination (R2), the value of R =0.582 means that the relationship between the independent variables on the purchasing decision variable is 23.9%, meaning a close relationship. The value of R square = 0.239 means that the influence of the independent variable (brand image) on the specified variable (purchase decision) is  23.9% and the remaining 76.1% is influenced by other variables that are not careful. Finallyfrom this study it can be said that the image has a positive and significant influence on purchasing decisions, so it is suggested to PT. Mahkota Jaya Sentosa Matahari Mall SKA Branch can improve brand image so that consumer purchasing decisions are even better to achieve company goals